2015
DOI: 10.1016/j.jinf.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Genomic resolution of an aggressive, widespread, diverse and expanding meningococcal serogroup B, C and W lineage

Abstract: SummaryObjectivesNeisseria meningitidis is a leading cause of meningitis and septicaemia. The hyperinvasive ST-11 clonal complex (cc11) caused serogroup C (MenC) outbreaks in the US military in the 1960s and UK universities in the 1990s, a global Hajj-associated serogroup W (MenW) outbreak in 2000–2001, and subsequent MenW epidemics in sub-Saharan Africa. More recently, endemic MenW disease has expanded in South Africa, South America and the UK, and MenC cases have been reported among European and North Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
242
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(252 citation statements)
references
References 27 publications
7
242
0
3
Order By: Relevance
“…Epidemiology has been dynamic in the last 5 years, with increased MenW circulation (W:2a:P1.5,2:ST-11 and W:2a: P1.2:ST-11 accounted for 78% of all isolates). In Argentina, the MenW strains are distinct from the MenW strain that was first identified in Europe following the Hajj pilgrimage in 2000 (the so-called Hajj outbreak strain) [35], as is also the case with the strains in Chile. Argentina recently announced the plan to introduce the quadrivalent conjugate vaccine for infants at 3, 5, and 15 months old, with an adolescent dose at 11 years.…”
Section: Latin Americamentioning
confidence: 89%
See 1 more Smart Citation
“…Epidemiology has been dynamic in the last 5 years, with increased MenW circulation (W:2a:P1.5,2:ST-11 and W:2a: P1.2:ST-11 accounted for 78% of all isolates). In Argentina, the MenW strains are distinct from the MenW strain that was first identified in Europe following the Hajj pilgrimage in 2000 (the so-called Hajj outbreak strain) [35], as is also the case with the strains in Chile. Argentina recently announced the plan to introduce the quadrivalent conjugate vaccine for infants at 3, 5, and 15 months old, with an adolescent dose at 11 years.…”
Section: Latin Americamentioning
confidence: 89%
“…In Brazil, MenC remains the most common cause of disease; disease due to MenW has not increased as much as in Argentina or Chile, although the same MenW strain is involved [35]. Infant immunization with MenC conjugate vaccine follows schedule of immunization at 3 and 5 months, with a booster dose at 12 months, and a single dose for toddlers ages 12-23 months, but without a 'catch-up' campaign in older age groups [36].…”
Section: Latin Americamentioning
confidence: 99%
“…38 Modeling showed that follow-up vaccine strategies were needed to maintain protection and helped to inform current WHO MenA vaccine recommendations for sub-Saharan Africa. 41 The reasons for this rapid expansion are unclear and further investigation is required. In addition, a number of groups in the United Kingdom and France have recently noted that MenW ST-11 is associated with some unusual symptoms, such as septic arthritis.…”
Section: Conducting Carriage Studiesmentioning
confidence: 99%
“…For instance, meningococci belonging to cc11 have been isolated as expressing either a serogroup B, serogroup C or serogroup W capsule 14 .…”
Section: Prevention Of Imdmentioning
confidence: 99%
“…The core genome of the meningococcus has been characterised and is defined by 1605 core loci 16 . Comparison of meningococcal core genomes has previously been used to characterise N. meningitidis isolates causing outbreaks and epidemics 14,17 . With the collaboration of PathWest and under the supervision of A/Prof Charlene Kahler (UWA), I was able to implement one such analysis in Australia, as described below.…”
Section: Prevention Of Imdmentioning
confidence: 99%